Pengaruh Brand Image dan Word of Mouth terhadap Keputusan Pembelian : Studi Kasus Maharani Cake House di Tangerang Selatan - Suryani Suryani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to uncover the relationship between Brand Image and Word of Mouth on consumer purchasing decisions at Maharani Cake House. With the background of a high number of people with disabilities in Indonesia, Maharani Cake House emerges as a solution for social inclusion and creating job opportunities for them. A strong brand image and word-of-mouth recommendations are considered to influence customer satisfaction. The research method used is quantitative descriptive with a questionnaire. The data analysis results show that Brand Image and Word of Mouth have a significant influence on purchasing decisions, in line with consumer theory. These findings are consistent with previous research stating that a strong brand image and social interaction play an important role in shaping purchasing decisions. The research conclusion emphasizes the importance of building a strong brand image and enhancing social interaction to improve customer satisfaction and brand loyalty. Therefore, it is recommended for companies to continuously strengthen their brand image and foster word of mouth to increase consumer trust and expand market share.